2011
DOI: 10.1089/end.2010.0627
|View full text |Cite
|
Sign up to set email alerts
|

Ex-VivoUreteroscopy at the Time of Live Donor Nephrectomy

Abstract: ExURS safely renders live donor kidney allografts stone free with low risk of recurrence. When used appropriately, ExURS could safely increase the number of potential kidney donors and minimize the risk of adverse stone events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…There are few case series which have shown that the short-and medium-term results are excellent both in donor and recipient follow-up after bench ureteroscopy [12][13][14][15][16][17][18]. We need long-term results with large number of patients to establish bench URS/RIRS as treatment of choice for this specific category of patients.…”
Section: Resultsmentioning
confidence: 99%
“…There are few case series which have shown that the short-and medium-term results are excellent both in donor and recipient follow-up after bench ureteroscopy [12][13][14][15][16][17][18]. We need long-term results with large number of patients to establish bench URS/RIRS as treatment of choice for this specific category of patients.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that there are no diagnostic and therapeutic standards with respect to detection and treatment of nephrolithiasis in donor kidneys [2,3]. In clinical practice, ultrasonography and CT of the abdomen can detect nephrolithiasis if present prior to transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate the findings of several studies that have demonstrated the safety and ease of performing ex-vivo ureteroscopy prior to renal implantation. 10,13,14 With regards to small renal masses, one patient with an incidentally discovered 2 cm AML underwent ex-vivo partial nephrectomy and renorrhaphy. Ex-vivo partial nephrectomy for incidentally discovered renal masses with subsequent renal implantation has been described previously, with several reports demonstrating its applicability to small renal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%